Strategi Komunikasi Humas PT. Medan-Binjai Toll dalam Membangun Citra Perusahaan Sebagai Pengelola Jalan Tol - Jordi Fahrezi; Muaz Tanjung (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study examines the public relations communication strategies of PT Medan–Binjai Toll in building a positive corporate image and managing crises in the digital age. Using a descriptive qualitative approach, this study is grounded in Frank Jefkins’ Image Theory and Grunig and Hunt’s Two-Way Symmetrical Communication Theory. Data were collected through in-depth interviews, non-participant observation, and documentation from the Instagram account (@medanbinjaitoll) and the official website (medanbinjaitollroad.com), and were then analyzed using the Miles and Huberman interactive model. The results show that public relations strategies were implemented by aligning three elements (Brand, Audience, Trend), the “Salam Sepakat: Setuju Patuhi Keselamatan” safety campaign, and two-way interactions that successfully shifted the “wish image” into a positive “current image.” The main obstacle—the lengthy bureaucratic approval process for internal press releases—was tactically overcome by issuing a 24-hour standby release. Additionally, crisis management was handled in an integrated manner through digital transparency, the use of Variable Message Signs (VMS), and immediate corrective actions on-site. This study concludes that building a positive image requires alignment between digital communication transparency, the efficiency of internal bureaucracy, and concrete actions on the ground.